APLIKASI BEBERAPA DOSIS INOKULUM SPORA Scleroderma columnare UNTUK MENINGKATKAN PERTUMBUHAN BIBIT MAHONI (Swietenia macrophylla) - Siti Suprehatin; Melya Riniarti; Duryat Duryat (Lambung Mangkurat University-Indonesia, 2019)
Mahagony is one of plants that could fill the needs of wood in Indonesia. The need of wood recently reached 10 million m3 per year. Basically Mahagony plants were very well associated with endomycorrhizal, but there was study that showed the Mahagony plants were able to associated with ectomycorrhizae spore. The aims of this studied were to determine the effected of ectomycorrhizae on Mahagony plant seedlings and the best dose of ectomycorrhyzae inoculation to improved the growth of Mahagony plants. This study was carried out in the greenhouse of the Faculty of Agriculture, University of Lampung on October 2017 - March 2018. The method used is completely randomized design with 4 treatments, 5 replications and 5 units of each experimental unit so that the entire plant amount were 100 experimental units. The dosage applied in this research were 0 ml/polybag, 10 ml / polybag, 20 ml / polybag and 30 ml / polybag. Parameters observed in this study were leaf area, height, diameter, number of leaves, root length, percentage of colonization, and dry weight. The research data obtained then analyzed using a homogenity test, Bartlett test and then proceed with smallest real difference test. The results showed that giving of ectomycorrhizae at a dose of 20 ml/polybag and 30 ml/polybag significantly affected to have higher percentage of colonization than the dose of 10 ml/polybag which is equal 0.67% to 0.84%. In leaf area parameter, the application of ectomycorrhizae with dossages of 30 ml.polybag, significantly showed the lowest leaf area compare to other treatments. It conclude that mahagony plants were not compatible with ectomycorrhizae there for percentage of inoculation in mahagony plants seeds was low and could not help plant grow.